Activated invariant natural killer T cells directly recognize leukemia cells in a CD1d‐independent manner. Issue 7 (19th June 2020) - Aoki, Takahiro; Takami, Mariko; Takatani, Tomozumi; Motoyoshi, Kiwamu; Ishii, Ayana; Hara, Ayaka; Toyoda, Takahide; Okada, Reona; Hino, Moeko; Koyama‐Nasu, Ryo; Kiuchi, Masahiro; Hirahara, Kiyoshi; et al.
Abstract: Invariant natural killer T (iNKT) cells are innate‐like CD1d‐restricted T cells that express the invariant T cell receptor (TCR) composed of Vα24 and Vβ11 in humans. iNKT cells specifically recognize glycolipid antigens such as α‐galactosylceramide (αGalCer) presented by CD1d. iNKT cells show direct cytotoxicity toward CD1d‐positive tumor cells, especially when CD1d presents glycolipid antigens. However, iNKT cell recognition of CD1d‐negative tumor cells is unknown, and direct cytotoxicity of iNKT cells toward CD1d‐negative tumor cells remains controversial. Here, we demonstrate that activated iNKT cells recognize leukemia cells in a CD1d‐independent manner, however still in a TCR‐mediated way. iNKT cells degranulated and released Th1 cytokines toward CD1d‐negative leukemia cells (K562, HL‐60, REH) as well as αGalCer‐loaded CD1d‐positive Jurkat cells. The CD1d‐independent cytotoxicity was enhanced by natural killer cell‐activating receptors such as NKG2D, 2B4, DNAM‐1, LFA‐1 and CD2, but iNKT cells did not depend on these receptors for the recognition of CD1d‐negative leukemia cells. In contrast, TCR was essential for CD1d‐independent recognition and cytotoxicity. iNKT cells degranulated toward patient‐derived leukemia cells independently of CD1d expression. iNKT cells targeted myeloid malignancies more than acute lymphoblastic leukemia. These findings reveal a novel anti–tumor mechanism of iNKT cells in targeting CD1d‐negative tumor cells and indicate the potential of iNKT cells for clinical application to treat leukemia independently of CD1d. Abstract : Activated human iNKT cells directly recognize leukemia cells, especially myeloid malignancies, in a CD1d‐independent manner. The CD1d‐independent cytotoxicity of iNKT cells depends on Vα24Vβ11‐T cell receptor and is enhanced by NK cell‐activating receptors.